CHARACTER VALUES CULTIVATION THROUGH MOVIE SING 2 ANIMATION - Sari, Damiana Septi Kartika; Triayomi, Ria (International Journal of Business, Law, and Education, 2023)
This research aims to perceive how to analyze the educational values of children’s characters in the Sing 2 animated movie. This research is qualitative research with a descriptive method. The data collecting technique used observation to analyze the Sing 2 animated movie. This research used the researchers’ triangulation to attain valid data. This research used Miles and Hubarman's analyzing data technique which has three steps namely, data reduction, data presentation, and conclusion. There are three researchers in this research. Based on the research findings, the researchers discovered 14 educational values of children’s characters in the Sing 2 animated movie which is suitable to 18 educational values from Syamsul Kurniawan’s book in 2017. The educational values that appear in the Sing 2 animated movie include honesty, tolerance, discipline, hard work, creativity, independence, curiosity, love for peace, patriotism, appreciation of achievements, communication, caring for society, and responsibility. The character's education presented in the Sing 2 animated movie can be used as a medium for nurturing character values through the learning process.